Traffic Management in 5G Mobile Networks: Selfish Users and Fair Network - Mahmoodi, Toktam; Jiang, Menglan (Discoveries in Agriculture and Food Sciences, 2016)
With increasing in heterogeneity of the mobile and wireless networks, including the use of licensed and unlicensed spectrum, and diversity in types of User Equipment (UEs), managing how traffic flows through network while maintaining high level of users’ quality of experience is crucial. In this paper, we present a novel traffic management mechanism that maintains the users’ quality of experience as well as guaranteeing fairness among users. This traffic management has two separate elements, one that is located at the UE and one that is located at the cloud-based network controller. While each UE maximizes their utility function, which is modelled based on the QoS parameters, selfishly, at the network side, the attempt is to maximize fairness among all users’ flows.